(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This qualitative research presents an artistic-pedagogical inventory of the practices and actions of artist-teachers in times of pandemic, in Rio de Janeiro, Brazil. It reflected, through a critical and hopeful outline, on what happened in the first semester of 2020 with the teaching of Drama in Basic Education in the state of Rio de Janeiro. Always attentive to the voices of teachers, and substantiated by theoretical-documentary references, this article identifies the protagonism of teachers who assumed, often without realizing it, the condition of researchers, authors, producers of emergency knowledge and protagonists of this unprecedented moment of our history.